Two family house [videorecording (DVD)] - DeFelitta, Raymond; Rispoli, Michael; Macdonald, Kelly, 1976- (Lions Gate Home Entertainment, 2003)
Buddy defies his wife and family to follow his dreams, and meets a woman who truly believes in him.